Book Review of Doing Educational Research in Rural Settings: Methodological Issues, International Perspectives and Practical Solutions - Ian Burfoot-Rochford (Journal of Research in Rural Education, 2015)
Doing Educational Research in Rural Settings: Methodological Issues, International Perspectives and Practical Solutions, edited by Simone White and Michael Corbett, provides an introduction to rural education research and represents one of the fi rst books to address the many methodological issues that emerge in this research. Collectively, the authors argue that rural education research must hono r and reveal that which is distinctive about rural schools and communities and the interrelationship between them. To do otherwise inevitably marginalizes rural places as defi cient, thus undermining their vitality and uniqueness. As the authors in this collection make clear, conducting research "for," rather than simply "on" rural places is of critical importance. Therefore, the research process should be shaped accordingly. Like many anthologies, this collection covers a range of diverse issues and themes that are not always consistently presented in a way that best serves the reader. In this book review, I highlight the palpable themes that emerged from the text, although the book itself does not follow this structure.